Effect of N-acetylcystein on ERK Gene Expression in Ovarian Tissue of Acrylamide-Treated Adult Rats - Marziyeh Naimi; Mehrdad Shariati; Sirous Naeimi; Mohammad Amin Edalatmanesh (Indonesian Center for Animal Research and Development (ICARD), 2020)
Acrylamide (AA) is a toxic and carcinogenic compound produced in cooking process. The purpose of this study is to evaluate the effect of N-acetylcysteine (NAC) on extracellular signal-regulated kinase (ERK) gene expression level and ovarian histopathological changes in AA-treated rats. Thirty-six female adult Wistar rats were randomly divided into 6 groups including control, positive control (+VE Con), negative control (-VE Con), experimental 1 (Exp1), experimental 2 (Exp2) and experimental 3 (Exp3). Twenty eight days after the treatment, ERK gene expression level was measured by real-time PCR method and ovarian histopathological changes were evaluated. The ERK gene expression level was significantly decreased in the +VE Con, Exp1 and Exp2 groups as compared to the control group (p˂0.05), but not in the -VE Con and Exp3 groups (p˃0.05). Histologically, the +VE Con group showed a significant decrease in the number of primary, secondary and Graafian follicles as well as corpus luteum as compared to the control group (p˂0.05), but not in the negative, Exp2 and Exp3 groups (p˃0.05). In the Exp1 group, the number of primary and secondary follicles as well as corpus luteum significantly decreased (p˂0.05), however, the numbers of Graafian follicle and the corpus luteum were significantly increased as compared to the +VE Con group (p˂0.05). The AA was supposed to increase the apoptosis and folliculogenesis degradation in the rat ovarian tissue by decreasing ERK gene expression. Administration of NAC ameliorated the deleterious effects of AA in a dose-dependent manner and improve folliculogenesis by reducing apoptosis level. Thus, the NAC supplement could be helpful in ameliorating animal fertility.